Response of linseed (Linum usitatissimum L.) varieties to different plant spacing and fertilizer levels: RESPONSE OF LINSEED VARIETIES TO DIFFERENT PLANT SPACING AND FERTILIZER LEVELS - S R GAIKWAD; V P SURYAVANSHI; A M MISAL (Journal of Oilseeds Research, 2019)
A field experiment was conducted during rabi 2016 in Vertisols at Oilseed Research Station, Latur to assess the response of  inseed varieties to different plant spacing and fertilizer levels. Number of branches/plant, spread/plant, dry matter accumulation/plant, number of capsules/plant, weight of capsule/plant, number of seeds/capsule, seed yield/plant, test weight, seed yield (kg/ha), harvest index (%) and oil content (%) were significantly higher with linseed variety LSL-93 over variety NL-260. All individual plant characters were higher with plant spacing of 30 cm x 10 cm. The spacing of 30 cm × 5 cm gave significantly higher seed yield over the spacing of 45 cm × 5 cm and 30 cm × 10 cm. The significant response to applied fertilizer was up to 100% recommended dose of fertilizer and this level produced higher seed yield and gross returns.